The Effect of Guarantee Value and Business Profit on the Decision to Provide Musharakah Financing at Bank Kalsel Sharia Banjarmasin Branch - Safitri , Dewi (UMBanjarmasin, 2024)
This study discusses the critical impact of the guarantee value and work benefits on the choice of granting musyarakah funds in Banjarmasin Syariah, Bank Kalsel Section. This exploration is a quantitative examination with a documentation data collection strategy and is handled again using the IBM SPSS 25 program, with various Direct Relapse test tools. This examination is directed at the Sharia Branch of Bank Kalsel Banjarmasin as an object of exploration. The consequence of this study shows that the value of Sig. Variable Assurance Worth (X1) is 0.131 > 0.05 and the tcount is 4.799 <12.706. Sig. Variable Work Benefit Benefits (X2) of 0.320 > 0.05 and a tcount of 1.822 <12.706. The consequences of the review show that at the same time the guarantee reward factor and work wages greatly influence the choice to provide musyarakah support at Bank Kalsel Banjarmasin Syariah Branch. This can be proven by the value of Fcount 35.166 > Ftable 0.053.